2000
DOI: 10.1159/000006642
|View full text |Cite
|
Sign up to set email alerts
|

Neural Connections of the Anterior Hypothalamus and Agonistic Behavior in Golden Hamsters

Abstract: In male golden hamsters, offensive aggression is regulated by an interaction between arginine-vasopressin and serotonin at the level of the anterior hypothalamus. The present studies were conducted to study a neural network underlying this interaction. The connections of the anterior hypothalamus were examined by retrograde and anterograde tracing in adult male hamsters. Several limbic areas were found to contain both types of tracing suggesting reciprocal connections with the anterior hypothalamus. Their func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(191 citation statements)
references
References 86 publications
13
174
2
2
Order By: Relevance
“…In addition, the present experiments provide novel data on Fos responses to STI and provide the first demonstration that aggressive behavior in birds correlates with IEG expression in the basal forebrain. Finally, we observed a pattern of IEG response that is consistent with patterns of IEG response that have been observed in rodents [19][20][21], suggesting that neural circuitry relevant to aggression has been strongly conserved during vertebrate evolution. A-E. Correlations between aggressive behavior (ln the number of barrier contacts during a 10-min observation) and Fos-ir cell counts in the ventral, ventrolateral and dorsal zones of the caudal lateral septum (LSc.v, LSc.vl and LSc.d; A-C, respectively), paraventricular hypothalamus (PVN; D), and anterior hypothalamus (AH; E) of male song sparrows exposed to a simulated territorial intrusion (n = 16).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the present experiments provide novel data on Fos responses to STI and provide the first demonstration that aggressive behavior in birds correlates with IEG expression in the basal forebrain. Finally, we observed a pattern of IEG response that is consistent with patterns of IEG response that have been observed in rodents [19][20][21], suggesting that neural circuitry relevant to aggression has been strongly conserved during vertebrate evolution. A-E. Correlations between aggressive behavior (ln the number of barrier contacts during a 10-min observation) and Fos-ir cell counts in the ventral, ventrolateral and dorsal zones of the caudal lateral septum (LSc.v, LSc.vl and LSc.d; A-C, respectively), paraventricular hypothalamus (PVN; D), and anterior hypothalamus (AH; E) of male song sparrows exposed to a simulated territorial intrusion (n = 16).…”
Section: Resultssupporting
confidence: 87%
“…In mammals, agonistic encounters elicit significant Fos responses within a similar suite of areas -the extended medial amygdala, LS (particularly the ventrolateral LS), AH, and lateral VMH/ ventrolateral hypothalamus [19][20][21]. Although these areas show increased IEG expression following agonistic encounters, it is not necessarily the case that these areas promote aggressive behaviors.…”
Section: Comparisons With Other Speciesmentioning
confidence: 99%
“…The nT in birds is homologous to parts of the mammalian amygdala and previous work has shown that this region plays an important role in regulating sexual and aggressive behaviors in mammals and birds (Thompson et al, 1998;Delville et al, 2000;Davis and Marler, 2004;Reiner et al, 2004). Interestingly, in nT AR-mRNA expression was increased during the nonbreeding season.…”
Section: Ar and Arom Expression In Ntmentioning
confidence: 90%
“…10 The PFC and hippocampus have been identified as particularly important in the modulatory control of subcortical circuits that mediate aggressive and impulsive behaviors 11,12 ; the components of these circuits include the medial amygdala, hypothalamus and the periaqueductal grey. [13][14][15][16][17][18][19][20][21][22] Indeed, PFC lesions promote an increase in aggressive behavior in rats. 23 Similarly, lesions involving frontal and temporal brain areas have been demonstrated to dramatically increase aggressiveness in humans.…”
Section: Introductionmentioning
confidence: 99%